2011
DOI: 10.1159/000335104
|View full text |Cite
|
Sign up to set email alerts
|

STAS Domain Structure and Function

Abstract: Pendrin shares with nearly all SLC26/SulP anion transporters a carboxy-terminal cytoplasmic segment organized around a Sulfate Transporter and Anti-Sigma factor antagonist (STAS) domain. STAS domains of divergent amino acid sequence exhibit a conserved fold of 4 β strands interspersed among 5 α helices. The first STAS domain proteins studied were single-domain anti-sigma factor antagonists (anti-anti-σ). These anti-anti-σ indirectly stimulate bacterial RNA polymerase by inactivating inhibitory anti-σ kinases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 75 publications
3
81
0
Order By: Relevance
“…Activation of ECFs occurs through inactivation of anti-sigma factors by STAS (sulfate transporter and anti-sigma factor antagonists) (57). In our study, we identified two STAS anti-sigma factor antagonists, LEPBIa2328 and its paralogue LEPBIa0072 (Id ϭ 39.4%, Pos ϭ 65.7%) (31)(32)(33)58). The importance of LEPBIa2328 in tolerance to EtBr is supported by the fact that we identified two independent mutants in this gene.…”
Section: Discussionsupporting
confidence: 54%
“…Activation of ECFs occurs through inactivation of anti-sigma factors by STAS (sulfate transporter and anti-sigma factor antagonists) (57). In our study, we identified two STAS anti-sigma factor antagonists, LEPBIa2328 and its paralogue LEPBIa0072 (Id ϭ 39.4%, Pos ϭ 65.7%) (31)(32)(33)58). The importance of LEPBIa2328 in tolerance to EtBr is supported by the fact that we identified two independent mutants in this gene.…”
Section: Discussionsupporting
confidence: 54%
“…The GigB protein contains a sulfate transport and anti-sigma factor antagonist (STAS) domain. In several other bacterial species, TCS-RRs harboring PP2C domains and STAS domaincontaining anti-anti-sigma factors function together to regulate the activity of antisigma factors, effectively functioning to activate alternative sigma factors (26)(27)(28)(29)(30). The Bacillus subtilis sigma B ( B ) regulatory system represents a well-characterized example of such a signal transduction pathway.…”
Section: Resultsmentioning
confidence: 99%
“…As described regarding other anti-sigma antagonists like RsbV from B. subtilis, SypA from V. fisheri, or HsbA from P. aeruginosa, CrsA contains the conserved STAS domain and a potentially phosphorylatable serine residue at position 49 ( Fig. 1A) (24,31,37,40). The second protein, CrsR (SO2119), is a 64-kDa protein that presents characteristics of an unusual response regulator.…”
Section: S Oneidensis Genome Contains Amentioning
confidence: 94%
“…In turn, the latter can thus associate with the RNA polymerase and can induce expression of its regulon. In this mechanism, the availability of the sigma factor depends on the phosphorylation state of the anti-sigma antagonist (30,31). Although partner-switching systems were initially unveiled in Gram-positive bacteria, they have also been found in some Gram-negative bacteria including Bordetella (BtrWVU), Vibrio fisheri (SypEA), and Pseudomonas aeruginosa (HsbRA).…”
mentioning
confidence: 99%